Exploring the low income rental housing market in the platinum mining sector for inclusive business opportunities - Makaula, Lulamile (Research of GSB, 2017)
The South African mining sector faces growing expectations from the academic, political, and regulatory spheres to play a greater role in facilitating development in communities affected by mining operations. The facilitation of affordable decent housing for lower-income employees is one of these expectations. In the South African platinum mining sector, the growth of informal settlements around mining operations presents various socio-economic challenges in need of innovative solutions. To date, mining companies have implemented various initiatives to improve housing and living conditions for lower-income mine employees. Yet these initiatives have not resulted in major improvements, arguably due to the complex nature of the housing market around mining operations. This complex housing market demands a greater understanding and consideration of inclusive business models such as the adaptation of collaborative consumption business models. In addition, scholarly literature on community development and corporate social responsibility has not given enough attention to the complex housing market in the platinum mining sector. I thus ask, what characterises the supply and demand of rental housing in the platinum mining sector, and how do suppliers and customers currently connect? I conducted 18 interviews with rental housing providers, migrant mine workers, and company group housing managers. Archival information in the form of company documents supplemented the interviews. Based on a case study of Anglo American Platinum's Amandelbult mining operation, I find that the low-income rental housing market is characterised by a critical shortage of rental housing stock, and suppliers and customers generally connect through informal peer to peer networks. This characteristic of the rental housing market shows that mining companies initiatives are constrained due to a limited understanding of complexities in this market, and it suggests an innovative financing approach to building rental housing stock as a more immediate opportunity than adapting a collaborative consumption based business model.